Interdigitated back contact solar cells with polycrystalline silicon on oxide passivating contacts for both polarities. (7th July 2017) - Haase, Felix; Kiefer, Fabian; Schäfer, Sören; Kruse, Christian; Krügener, Jan; Brendel, Rolf; Peibst, Robby
Abstract: We demonstrate an independently confirmed 25.0%-efficient interdigitated back contact silicon solar cell with passivating polycrystalline silicon (poly-Si) on oxide (POLO) contacts that enable a high open circuit voltage of 723 mV. We use n-type POLO contacts with a measured saturation current density of J 0n = 4 fA cm −2 and p-type POLO contacts with J 0p = 10 fA cm −2 . The textured front side and the gaps between the POLO contacts on the rear are passivated by aluminum oxide (AlO x ) with J 0AlO x = 6 fA cm −2 as measured after deposition. We analyze the recombination characteristics of our solar cells at different process steps using spatially resolved injection-dependent carrier lifetimes measured by infrared lifetime mapping. The implied pseudo-efficiency of the unmasked cell, i.e., cell and perimeter region are illuminated during measurement, is 26.2% before contact opening, 26.0% after contact opening and 25.7% for the finished cell. This reduction is due to an increase in the saturation current density of the AlO x passivation during chemical etching of the contact openings and of the rear side metallization. The difference between the implied pseudo-efficiency and the actual efficiency of 25.0% as determined by designated-area light current–voltage ( I – V ) measurements is due to series resistance and diffusion of excess carriers into the non-illuminated perimeter region.